Fundamentals of creation of newdevices for speed change management - Malashchenko, Volodymyr; Strilets, Oleh; Strilets, Volodymyr (Publishing House of Lviv Polytechnic National University, 2015)
The article deals with problem of speed change management in engineering, i.e., hoisting, building, road and land reclamation machines, cars and tractors, machine tools and other equipment. The review of the methods and devices for stepped, steppless and combined speed change process management have been performed. Their major disadvantages have been identified. Among others, main disadvantages of stepped speed management devices are the complexity of design, their large material consumption, the emergence of dynamic loads during the transition from one speed to another, even in case of synchromesh using. Continuously variable speed devices have intense components wear due to the use of friction connections like brakes or lock-up clutches. The authors lead to the conclusion about the need for new devices of speed change management to remove, or at least decrease, identified deficiencies. New devices suggested for speed changes management via epicyclic gear trains with a closed circuit hydrosystem. Those new constructions are supposed to remove abovementioned shortcomings and can be the basis and foundation for new devices creation and their further research.